Perceptions of Undergraduate Physical Chemistry Instructors: Lessons from a Nationwide Survey, Assessment Analysis, and Reflections on Teaching and Learning - Fox, Laura (My University, 2016)
There are minimal policies in place that direct undergraduate education, and consequently there are scarce criteria that guide the pedagogical and curricular decisions of instructors. Thus, given their great degree of autonomy, instructors play a critical role in undergraduate education. In this dissertation, the perceptions of undergraduate physical chemistry instructors were investigated in three distinct, yet related studies, in order to understand how instructors’ beliefs and attitudes impact their role as educators. First, a nationwide survey of the undergraduate physical chemistry course was conducted to investigate the depth and breadth of course content, as well as how content is delivered and assessed. The results of the survey showed that a core group of thermodynamics and quantum mechanics topics were covered by almost all instructors, however there was a larger group of topics with a wide variability of coverage. Also, the majority of instructors created an instructor–centered environment, despite their degree of teacher preparation experience, and gave more mathematical assessment questions, which contradicted their conceptual leaning goals. Ultimately, the goal of the first study was to provide an awareness of the current state of physical chemistry education across the United States. Second, an analysis of physical chemistry assessments was conducted to investigate characteristics of assessment questions including format, type of knowledge, and type of cognitive processes. The assessment analysis found that instructors used a subjective format more often than an objective format, there was an approximate equal distribution among questions that elicited factual, conceptual, and procedural knowledge, and the majority of questions utilized simple cognitive processes. Ultimately, the goal of the second study was to examine assessment practices of physical chemistry instructors across the United States. Third, instructor reflections were utilized to investigate instructors’ pedagogical content knowledge. Reflection questions were designed to elicit various components of pedagogical content knowledge, as well as how components of pedagogical content knowledge are associated with successful teaching moments, challenging teaching moments, and proposed changes. The analysis of reflections showed that instructors had a strong orientation towards teaching, a varied knowledge of curriculum, a weak knowledge of students’ understanding, and a constantly evolving knowledge of instructional strategies. Ultimately, the goal of the third study was to use instructor reflections to provide a rich description of their pedagogical content knowledge. Together, the three studies of this dissertation helped broaden the landscape of physical chemistry education research. The diverse levels of scale, ranging from nationwide perspectives to individual viewpoints, as well as varied methodologies, including both quantitative and qualitative approaches, helped expand and transform physical chemistry education research.
University of Minnesota Ph.D. dissertation. May 2016. Major: Education, Curriculum and Instruction. Advisor: Gill Roehrig. 1 computer file (PDF); xi, 150 pages.
Keywords: Assessment; Chemical Education; Pedagogical Content Knowledge; Physical Chemistry; Survey; Undergraduate